Problems of legal regulation of GA of Canada and Ukraine - Зуєва, Вікторія Олександрівна; Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article compares the legal regulation of general aviation of the two countries: Ukraine and Canada. The state of development of this branch of civil aviation is analyzed, the problems that impede the development of the ARP in our country and the opportunities provided by this branch of aviation for the development of various sectors of the economy are identified.